A second-generation, self-amplifying COVID-19 Vaccine: World’s first approval and distribution in the Japanese market with vaccine hesitancy - Toshio Naito (Human Vaccines & Immunotherapeutics)
The mRNA vaccine is a milestone in immunotherapeutics, as symbolized by the 2023 Nobel Prize for Physiology or Medicine awarded to Drs. Karikó and Weissman. Whereas the conventional, “first-generation” mRNA vaccine was globally distributed to hundreds of millions of people to decrease COVID-19 prevalence, further advanced constructs have been pursued by researchers and pharmaceutical manufacturers. The key feature of the “second-generation” mRNA vaccine is a self-amplifying replicon that may allow a low dose to ensure durable immunogenicity. In clinical trials, ARCT-154 indeed showed effectiveness (magnitude, persistence, and breadth) superior to conventional mRNA vaccines, with similar or less frequent adverse responses, and acquired its world’s first approval in November 2023 in Japan (brand name: KOSTAIVE manufactured by Meiji Seika Pharma, Tokyo, Japan) to prevent COVID-19 infection. Real-world distribution of KOSTAIVE was started in October 2024, and researchers are collecting data on its effectiveness and safety despite nonscientific, but persistent, antivaccine skepticism.